PENGARUH PROFIL PERUSAHAAN TERHADAP HUBUNGAN ANTARA PRAKTIK PENGUNGKAPAN SOSIAL DAN NILAI PERUSAHAAN - SURYANTO SURYANTO (Jurnal Bisnis dan Akuntansi, 2013)
The purpose of this study is to investigate social disclosure practice diferrence between high profile and low profile company and its effect on firm value. This study employs company profile as moderating variable to explain the effect of social disclosure on firm value.Data for this study are acquired from annual report of public companies in Indonesia over two years period (2009-2010) and also from yahoo finance in collecting market price of each company share. Regression model is used to this study.The result for this study is as follows. First, social disclosure has effect to firm value. Second, company profile has no effect to firm value and also to relationship between social disclosure and firm value. This result indicate if company profile fails to contribute in determining social disclosure practice, so that company profile fails to give effect on relationship between social disclosure and firm value.